Perancangan Sistem Informasi Produksi Baru untuk Bagian Manufaktur SPP di PT X - Elsa Puspa Sari Wibisono; Iwan Halim Sahputra (Jurnal Titra, 2020)
SPP is a section of PT X manufacturing that produces packaging. KPI (Key Performance Indicators) of SPP are safety and sustainability, quality, delivery, and cost. Cost is divided into DIM (direct material) waste and productivity. DIM waste data percentage is recorded in the SPP production information system, including production report and material report. The problem is there is gap between the percentage of DIM waste in the production report and in the material report. This is caused by the three weaknesses of the SPP production information system. The SPP information system is not simple, the records are inaccurate, and not standard. The design of a new production information system is carried out in order to amend the weaknesses of the old production information system. This can support the company to minimize the gap between the percentage of DIM waste in the production report and in the material report results.